TARGETED PROSTATE BIOPSY: TECHNIQUES, CLINICAL OUTCOMES, AND FUTURE PERSPECTIVES – A NARRATIVE REVIEW - Oliwia Krawczyk; Paulina Dybiak; Adrian Morawiec; Paweł Słoma; Maciej Zachara; Mateusz Bartoszek; Patryk Harnicki; Mikołaj Grodzki; Jakub Minas; Erwin Grzegorzak; Rafał Pelczar (International Journal of Innovative Technologies in Social Science, 2026)
Prostate cancer is one of the most frequently diagnosed malignancies among men worldwide and continues to pose a major clinical and public health challenge (Rawla, 2019; Pernar et al., 2018). Despite substantial advances in screening and imaging, accurate identification of clinically significant prostate cancer remains a critical issue in contemporary urologic practice. Conventional systematic transrectal ultrasound-guided biopsy has long been considered the diagnostic standard; however, it is inherently limited by random sampling error and is associated with both underdiagnosis of aggressive disease and overdiagnosis of indolent tumors (Schoots et al., 2017; Kasivisvanathan et al., 2018). The integration of multiparametric magnetic resonance imaging (mpMRI) into prostate cancer diagnostic pathways has led to the development of targeted prostate biopsy techniques aimed at improving diagnostic accuracy and risk stratification (Padhani et al., 2019; Turkbey et al., 2022). This narrative review summarizes current evidence on targeted prostate biopsy, including the epidemiological and diagnostic background of prostate cancer, imaging foundations, biopsy techniques, clinical outcomes, and emerging innovations. A structured literature search was conducted using PubMed, ScienceDirect, and Google Scholar. The reviewed literature demonstrates that MRI-targeted biopsy improves detection rates of clinically significant prostate cancer while reducing the identification of clinically insignificant disease compared with systematic biopsy alone (Ahdoot et al., 2020; Drost et al., 2019). Targeted prostate biopsy has become a cornerstone of modern prostate cancer diagnostics, with ongoing research focusing on technique optimization, patient selection, and personalized diagnostic strategies.